VILJOEN, Johannes Hendrikus Inventory of documents - VILJOEN, Johannes Hendrikus (ARCA, 2018)
Private papers of J.H. Viljoen, National Party MP Hoopstad [1933-1934], United Party MP Hoopstad [1934-1941], Afrikaner Party [1941-1943], National Party MP Vryburg [1948-1957], Minister of Mines [1950-1953], Education Arts and Science [1950-1957], Social Welfare [1953-1954], Forestry [1954-1956] Health [1956-1957].
COVERAGE 1913-1958; 35 Files; 0,33 Metres.
Keywords: VILJOEN, Johannes Hendrikus; Inventories; Politicians; National Party